Модель функционального поражения подземных многопроводных радиочастотных линий связи мощными электромагнитными излучениями - Кучер, Д. Б.; Харланов, А. И.; Медведь, И. В.; Литвиненко, Л. В.; Корощенко, Н. Н. (НТУ "ХПИ", 2009)
The mathematical model of strong electromagnetic radiation influence on underground multiwired radiofrequency cable communication is presented. The problem of mutual interaction of wires is discussed too. As well as results of calculations of energy discharged on dielectric materials according to levels of voltages of strong electromagnetic radiations.
Keywords: электромагнитное излучение; кабель; проводники; подземная линия связи